Experimental and theoretical insights into enhanced light harvesting in dye-sensitized solar cells via Au@TiO2 core-shell and BaTiO3 nanoparticles - Paranthaman V.; Devi K.S.S.; Bhojanaa K.B.; Aravindan V.; Raman G.; Kumar R.S.; Doroody C.; Rajamony R.K.; Krishnan P.S. (Taiwan Institute of Chemical Engineers, 2025)
Background: Dye-sensitized solar cells (DSSCs) are an attractive choice among third-generation solar cells due to their affordability and eco-friendliness, making them a promising solution for sustainable energy production. Enhancing the light-capturing efficiency of photoanodes is crucial for improving the power conversion efficiency (PCE) of DSSCs. Methods: In this study, we developed core-shell Au@TiO2 (ATO) particles to enhance light harvesting and BaTiO3 (BTO) nanoparticles to act as a scattering layer. These nanoparticles were incorporated into a photoanode, paired with a commercial N719 sensitizer, an iodide/triiodide redox liquid electrolyte, and a Pt cathode. The performance of the assembled DSSC was compared with traditional TiO2 photoanodes, and further theoretical analysis was conducted using the solar cell capacitance simulator (SCAPS-1D) to examine PCE variations with ATO layer thickness (2?20 ?m). Significant findings: The DSSC with an ATO/BTO-based photoanode achieved a PCE of 8.76 %, significantly higher than the 6.72 % PCE of cells using bare TiO2 photoanodes. This efficiency enhancement is attributed to improved light scattering, reduced charge recombination, and minimized core particle corrosion due to the perovskite oxide layer. Enhanced plasmonic effects also led to superior light absorption and improved charge carrier generation and separation. ? 2024 Taiwan Institute of Chemical Engineers